The role of job satisfaction as a mediator in the relationship between family support and turnover intention - Sekar Dwi Ningrum; Rahmi Lubis; Suaidah Lubis (Jurnal Konseling dan Pendidikan, 2026)
High levels of turnover intention remain a critical issue in organizations, yet existing studies have predominantly focused on workplace factors while overlooking the role of family-based resources. Drawing on the Job Demands–Resources (JD-R) framework, this study addresses this gap by examining family support as an external resource and its influence on turnover intention through job satisfaction. This study aims to analyze the mediating role of job satisfaction in the relationship between family support and turnover intention among employees. A quantitative explanatory design was employed with a sample of 456 employees of PT. XYZ, selected using a proportional sampling technique. Data were collected through validated and reliable questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that family support has a significant positive effect on job satisfaction and a significant negative effect on turnover intention. Job satisfaction also shows a significant negative effect on turnover intention and partially mediates the relationship between family support and turnover intention. These findings demonstrate that family support not only directly reduces employees’ intention to leave but also indirectly influences it by enhancing job satisfaction. Theoretically, this study extends the JD-R framework by integrating family support as an external resource that contributes to employee retention mechanisms. Practically, the findings emphasize the importance of incorporating family-supportive policies to strengthen job satisfaction and reduce turnover intention, thereby promoting organizational sustainability.